1999
DOI: 10.1097/00005392-199901000-00078
|View full text |Cite
|
Sign up to set email alerts
|

Renal Transplantation in Children With Severe Lower Urinary Tract Dysfunction

Abstract: Renal transplantation may be successfully performed in children with end stage renal disease due to severe lower urinary tract dysfunction. Bladder reconstruction, which may be required in the majority of these cases, appears to be safe when performed before or after the transplant. A multidisciplinary team approach to surgery is advantageous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0
13

Year Published

2001
2001
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(69 citation statements)
references
References 21 publications
2
54
0
13
Order By: Relevance
“…Alfrey et al reported that bladder augmentation before transplant caused increasing hydronephrosis and infection and sug- Values are given as mean ± standard error unless indicated otherwise gested takedown of bladder augmentation before transplant [20]. Other studies, however, have shown that urinary tract reconstruction before transplantation is safe [21][22][23]. Koo et al studied 18 patients with severe dysfunctional lower urinary tract anomalies that included posterior urethral valves, urogenital sinus anomalies, prune-belly syndrome, complete bladder duplication, and ureterocele [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alfrey et al reported that bladder augmentation before transplant caused increasing hydronephrosis and infection and sug- Values are given as mean ± standard error unless indicated otherwise gested takedown of bladder augmentation before transplant [20]. Other studies, however, have shown that urinary tract reconstruction before transplantation is safe [21][22][23]. Koo et al studied 18 patients with severe dysfunctional lower urinary tract anomalies that included posterior urethral valves, urogenital sinus anomalies, prune-belly syndrome, complete bladder duplication, and ureterocele [22].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies, however, have shown that urinary tract reconstruction before transplantation is safe [21][22][23]. Koo et al studied 18 patients with severe dysfunctional lower urinary tract anomalies that included posterior urethral valves, urogenital sinus anomalies, prune-belly syndrome, complete bladder duplication, and ureterocele [22]. Eleven patients underwent bladder augmentation or continent urinary diversion, while two had an intestinal conduit and five had a transplant into the native bladder.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes only a brief referral is given about these complications in publications about graft survival. A summary of complications in pediatric patients reported in the literature and our own series is given in table 1 [2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12]. …”
Section: Discussionmentioning
confidence: 99%
“…Although rejection is the main cause of graft failure, urological complications can also play a role in graft loss and even patient mortality. The incidence of urological complications after kidney transplantation has been reported to range from 0 to 33% [2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13], although data are not really comparable because some authors include only major urological complications, whereas others even include urinary tract infections. A higher rate of complications can be expected in children compared with adults, due to the higher number of patients with congenital urinary tract abnormalities often seen in combination with bladder dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of bladder dysfunction after renal transplantation have been reported in adults [10]. There are several reports on post-transplant patient and graft survival [11][12][13][14][15][16] and a few on bladder function [17,18] in children with dysfunctional urinary tract, but there are, to our knowledge, no reports on bladder function in post-transplant children with normal urinary tracts. We report here the incidence of bladder dysfunction in an unselected group of renal transplant recipients in the Children's Hospital at Karolinska University Hospital, Huddinge, Sweden.…”
Section: Introductionmentioning
confidence: 98%